2020
DOI: 10.1111/cns.13427
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline mediates the NLRP3/IL‐1β signaling axis in microglia to alleviate ischemic blood‐brain barrier permeability by downregulating astrocyte‐derived VEGF in rats

Abstract: Introduction The aim of this study was to explore whether the antibrain edema of hypertonic saline (HS) is associated with alleviating ischemic blood‐brain barrier (BBB) permeability by downregulating astrocyte‐derived vascular endothelial growth factor (VEGF), which is mediated by microglia‐derived NOD‐like receptor protein 3 (NLRP3) inflammasome. Methods The infarct volume and BBB permeability were detected. The protein expression level of VEGF in astrocytes in a transient focal brain ischemia model of rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Blood–brain barrier disruption is the key pathophysiological basis for HT after stroke, 7,17 in the present study, two‐ and three‐dimensional electron microscopy revealed that hyperglycemia increased intracellular vesicles and enhanced endocytosis pathways in BMECs, contributing to increased BBB permeability after mild cerebral I/R injury, and concurrently, the risk of HT becomes more significant. The increase of endothelial vesicle numbers was the most prominent in the NVU in the post‐MCAO striatum, which harbored the most severe BBB breakdown.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Blood–brain barrier disruption is the key pathophysiological basis for HT after stroke, 7,17 in the present study, two‐ and three‐dimensional electron microscopy revealed that hyperglycemia increased intracellular vesicles and enhanced endocytosis pathways in BMECs, contributing to increased BBB permeability after mild cerebral I/R injury, and concurrently, the risk of HT becomes more significant. The increase of endothelial vesicle numbers was the most prominent in the NVU in the post‐MCAO striatum, which harbored the most severe BBB breakdown.…”
Section: Discussionsupporting
confidence: 54%
“…HG is associated with larger infarct size, more severe brain edema, poorer clinical outcome, and a higher risk of mortality and hemorrhagic transformation (HT). The mechanisms underlying increased occurrence of post‐stroke HT under HG condition are not fully understood, but exacerbation of blood–brain barrier (BBB) damage may play a crucial role 2‐7 . High blood glucose leads to endothelial cell dysfunction and increased intracellular reactive oxygen species (ROS), which are involved in a plethora of pathophysiological changes such as inhibition of nitric oxide (NO) synthesis, vascular inflammation, insulin resistance, neovascularization, leukocyte adhesion, and protein and polymer glycosylation 8‐12 .…”
Section: Introductionmentioning
confidence: 99%
“…A stable internal environment is necessary for normal nerve function 1,2 . Damage to the blood‐brain barrier is a major part of the pathophysiological process of many nervous system diseases, such as multiple sclerosis, stroke, Alzheimer's disease, vascular dementia, cerebral small vessel disease, traumatic brain injury, and epilepsy 3‐12 …”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory signaling in M1 microglia involves toll‐like receptor (TLR)‐4, 25,105 the IFN‐γ receptor complex, 106 the granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) receptor, 107 and COX2 108‐110 . The secretion of TNF‐α, IL‐1β, IL‐6, IL‐12, CCL2, and CXCL10 is shown to change TJs (claudin‐5, occludin, ZO‐1, and ZO‐2) and critical BBB transporters like P‐gp proteins 18,26,102,111‐114 . Besides, the chemokines CCL2 and CXCL10 promote trafficking of immune cells cross the BBB, including monocytes and macrophages, which is observed in stroke 115,116 .…”
Section: Mechanisms Of Peripheral Inflammation‐induced Bbb Disruptionmentioning
confidence: 99%